2018
DOI: 10.3233/blc-180179
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers in the Evaluation of Primary Hematuria: A Systematic Review and Meta-Analysis

Abstract: Introduction: Urinary biomarkers are entering the clinical landscape as a non-invasive method to evaluate patients for bladder cancer, however it is currently predominantly used in the surveillance setting. The use of biomarkers in the setting of primary hematuria is not widespread despite initial promising results. This study comprehensively reviews the literature on the diagnostic performance of FDA-approved biomarkers in the evaluation of primary hematuria.Methods: According to the Preferred Reporting Items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…There are two approved versions of this test for BCa follow-up in concurrent use with cystoscopy, the BTA TRAK and the BTA Stat (Polymedco Inc., Cortlandt Manor, New York, USA) [ 63 ]. In different reviews and meta-analysis, the BTA Stat has a sensitivity and specificity of 64% and 77%, respectively, whereas the BTA Trak has 65% and 74%, respectively [ 64 , 65 , 66 ]. The sensitivity was higher in the diagnosis of symptomatic patients rather than in follow-up, but with similar specificity.…”
Section: Liquid Biopsy As a Source Of Biomarkers For Bladder Cancementioning
confidence: 99%
See 2 more Smart Citations
“…There are two approved versions of this test for BCa follow-up in concurrent use with cystoscopy, the BTA TRAK and the BTA Stat (Polymedco Inc., Cortlandt Manor, New York, USA) [ 63 ]. In different reviews and meta-analysis, the BTA Stat has a sensitivity and specificity of 64% and 77%, respectively, whereas the BTA Trak has 65% and 74%, respectively [ 64 , 65 , 66 ]. The sensitivity was higher in the diagnosis of symptomatic patients rather than in follow-up, but with similar specificity.…”
Section: Liquid Biopsy As a Source Of Biomarkers For Bladder Cancementioning
confidence: 99%
“…The sensitivity was higher in the diagnosis of symptomatic patients rather than in follow-up, but with similar specificity. Both tests demonstrated higher sensitivity than urinary cytology, despite the decreased specificity in conditions where the complement factor H related protein is present, such as in other genitourinary malignancies and benign conditions with hematuria, including lithiasis, inflammation, instrumentation, and intra-vesical therapies [ 31 , 64 , 65 , 66 , 80 ].…”
Section: Liquid Biopsy As a Source Of Biomarkers For Bladder Cancementioning
confidence: 99%
See 1 more Smart Citation
“…Urine cytology in conjunction with cystoscopy is considered to be the 'gold standard' and is recommended in the European Guidelines for high‐risk non‐muscle‐invasive bladder cancer (NMIBC). The excellent specificity of urine cytology is well documented; however, the reported sensitivity has been extremely variable [2]. Whilst, historically, cytology was thought to have good sensitivity for high‐grade disease, with reported sensitivities of between 38% and 84% [3], recently, larger multicentric studies have demonstrated much lower sensitivities, with a prospective study of 1016 patients demonstrating an overall sensitivity of 22%, 13% for low‐grade tumours, 23% for high‐grade tumours and 25% for high‐risk tumours [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…UroVysion was developed as an adjunct to cytology and is a fluorescence in-situ hybridisation (FISH) analysis of urine cytology, which detects specific genetic amplifications in urothelial cells. Sensitivity is better than for cytology, but still too low to be used to exclude further investigations, and it still suffers from a high inter-observer variability [4]. Recently, newer mRNAand epigenetic-based assays have been reported and made commercially available.…”
mentioning
confidence: 99%